Development of Traditional Game-Based Mathematical Tools for Elementary School Students - Andayani; Zakirman; Alpin Herman Saputra; Suryo Prabowo; Eri Irianto (Universitas Djuanda, 2022)
This research and development aim to 1) determine the feasibility of developing mathematics learning media using traditional game-based mathematical tools and 2) determine the attractiveness of students' responses to the development of mathematics learning media using Traditional game-based mathematical tools. This research was carried out using the Research and Development (R and D) method using the modified Borg and Gall development procedure, and data collection techniques using a validation questionnaire sheet. The instrument used was a validation questionnaire sheet to determine the feasibility of the module and a questionnaire for student responses to find out the interest. Data analysis techniques used in research and development are quantitative descriptive to process data in the form of scores from the validator's assessment and student response, while qualitative descriptive to describe the data in the form of commentary suggestions for improvement from the validator. Based on the results of the validation of the development of mathematics learning media using the Traditional game-based mathematical tools, an average score was obtained; (1) the feasibility of developing mathematics learning media using traditional game-based mathematical tools results of the validation of material experts obtained an average of 3.73, on linguistic aspects obtained an average of 3.64, on the aspect of feasibility evaluation obtained an average of 3.66, on media experts obtained on average (aspects of media efficiency obtained an average of 3.87, (2) attracting the development of mathematics learning media using the traditional game-based mathematical tools students' responses obtained an average score of 3.61 in the